HETEROSIS STUDIES IN HYBRID RICE (ORYZA SATIVA L.) OVER LOCATIONS - P. V. PADMAVATHI; P. V. SATYANARAYANA; M.LAL AHAMED (The Bioscan, 2013)
The present study was carried out to investigate the extent of standard heterosis and to identify promising hybrids with high magnitude of heterosis for yield and yield contributing traits. Fifty two hybrids were generated in line × tester mating fashion and evaluated in randomized block design along with parents and checks over locations. The assessment of heterosis showed significant results for all the traits. Eighteen hybrids exhibited significant standard heterosis for grain yield plant-1 and top among them were APMS 6A × MTU II-110-9-1-1-1-1, APMS 10A × MTU II-290-42-1 and APMS 9A × MTU II-143-26-2. These hybrids were also found significantly positive standard heterosis for yield components like number of panicle bearing tillers plant-1, panicle length, number of filled grains panicle-1 and test weight. The above top performing hybrids may be used for commercial exploitation.